OUR DIFFICULT WAY TO LOCAL GOVERNMENT (REFLECTION) - Gabdualiev , Мереке Тлекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The author of the present publication investigates some conceptual questions of institute of local government in the Republic of Kazakhstan, standards of the Constitution about local government, and also analyzes stages of development of the local government, reflected in the corresponding Concept.